The Toyota kata practice guide : practicing scientific thinking skills for superior results in 20 minutes a day - Rother, Mike (McGraw Hill Education, 2018)
Taking you to the next level of developing business mindset and capability for the 21st Century, this groundbreaking book walks you through the process of making improvement, adaptation, and even innovation routine behavior. --